Transphyseal Anterior Cruciate Ligament Reconstruction in the Skeletally Immature: Quadriceps Tendon Autograft Versus Hamstring Tendon Autograft. Issue 9 (17th September 2019) - Pennock, Andrew T.; Johnson, Kristina P.; Turk, Robby D.; Bastrom, Tracey P.; Chambers, Henry G.; Boutelle, Kelly E.; Edmonds, Eric W.
Background: It is unclear what the optimal graft choice is for performing anterior cruciate ligament (ACL) reconstruction in a skeletally immature patient. Purpose: To evaluate outcomes and complications of skeletally immature patients undergoing transphyseal ACL reconstruction with a hamstring tendon autograft versus a quadriceps tendon autograft. Study Design: Cohort study; Level of evidence, 3. Methods: Between 2012 and 2016, 90 skeletally immature patients from a single institution underwent primary transphyseal ACL reconstruction with either a quadriceps tendon autograft or a hamstring tendon autograft based on surgeon preference (n = 3). Patient demographic, injury, radiographic, and surgical variables were documented. Outcome measures included the Lysholm score, Single Assessment Numeric Evaluation (SANE), Tegner activity score, pain, satisfaction, and complications such as graft tears and physeal abnormalities. Results: A total of 83 patients (56 hamstring tendon, 27 quadriceps tendon) were available for a minimum follow-up of 2 years or sustained graft failure. The mean age of the patients was 14.8 ± 1.4 years at the time of ACL reconstruction. No differences in chronological age, bone age, sex, patient size, or mechanism of injury were noted between groups. There were no differences in surgical variables, except that the quadriceps tendon grafts were larger than the hamstring tendon grafts (9.6 ± 0.6 mm vs 7.8 ± 0.7 mm, respectively; P < .001). Patient outcomes at a mean follow-up of 2.8 ± 0.9 years revealed no differences based on graft type, with mean Lysholm, SANE, pain, satisfaction, and Tegner scores of 96, 93, 0.6, 9.6, and 6.6, respectively, for the quadriceps tendon group and 94, 89, 0.9, 9.2, and 7.1, respectively, for the hamstring tendon group. While there were no physeal complications in either group, patients undergoing ACL reconstruction with a hamstring tendon autograft were more likely to tear their graft (21% vs 4%, respectively; P = .037). Conclusion: Skeletally immature patients undergoing ACL reconstruction can be successfully managed with either a quadriceps tendon autograft or a hamstring tendon autograft with good short-term outcomes, high rates of return to sport, and low rates of physeal abnormalities. The primary differences between grafts were that the quadriceps tendon grafts were larger and were associated with a lower retear rate. ACL reconstruction performed with a quadriceps tendon autograft may reduce early graft failure in skeletally immature patients.